Rational Choice Theory in the Study of Deepwater Horizon Oil Spill - Verdinand Robertua; Angel Damayanti (Journal Research of Social Science, Economics, and Management, 2022)
The Deepwater Horizon oil spill was the worst environmental disaster in US history. The oil spill reflects the dependence of the United States on the exploitation of fossil fuels. President Barack Obama seeks to bring about significant changes in US energy policy by promoting and expanding clean energy. However, the new policy faced resistance from Congress and the oil companies. This study aims to determine the impact of the Deepwater Horizon Oil Spill on US energy policy using rational choice theory. To achieve the expansion of rational choice theory in the Deepwater Horizon oil spill study, the researcher used qualitative methodology and case study method. The result of this study is that the Deepwater Horizon oil spill became a stepping stone for the transformation of US energy policy. The findings of this study are the linearity of clean energy development and US political commitment in developing the clean energy industry.